Hubungan Pengetahuan Masyarakat Tentang Pentingnya Cuci Tangan 6 Langkah Terhadap Penularan Covid-19 Di Desa Telukjaya Pakisjaya Karawang Tahun 2020 - Pelawi, Arabta M. Peraten; Aulia, Fhikka; Moeljono, Eddy (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Coronaviruses are some of the groups of viruses that cause diseases ranging from mild to severe symptoms. There are two types of coronavirus known to cause diseases that can cause severe symptoms such as Middle East Respiratory Syndrome and Severe Acute Respiratory Syndrome. The increase in Covid-19 cases today is because many people do not understand how to transmit this virus. One of them with prevention against transmission of this virus can be done by the community by doing hand washing 6 steps. This study aims to find out if there is a relationship of public knowledge about the importance of hand washing 6 steps to the transmission of covid-19 in Telukjaya Pakisjaya Karawang Village. This research is a type of quantitative research with observational analytical design through a cross sectional approach. Sampling using probability sampling with a type of simple random sampling with a total of 144 respondents. The results showed (P value 0.000 < alpha value 0.05). Showing the relationship of public knowledge about the importance of hand washing 6 steps to the transmission of Covid-19 in Telukjaya Pakisjaya Karawang Village 2020.